Modelling the response of Bambara groundnut (Vigna subterranea (L.) Verdc) for abiotic stress - Karunaratne, Asha Sajeewani (2009)
Bambara groundnut (Vigna subterranea (L.) Verdc) is an indigenous legume that is still cultivated in subsistence agricultural systems in sub-Saharan Africa, despite the lack of any major research effort until recently. The crop is cultivated from local landraces as there are no true varieties of the species bred for specific traits. The variable and hostile climates in the region mean that annual yields of most rainfed crops including bambara groundnut are far below their agronomic or genetic potential. The lack of quantitative information on the eco-physiological responses of the crop to various abiotic factors has resulted in poor decision making on crop management practices especially in relation to sowing date and the selection of appropriate landraces for different locations. Modelling of bambara groundnut was initiated previously but there is still insufficient understanding of how growth and developmental processes can be simulated under abiotic stress and different photoperiods. The aim of this study was to develop a crop simulation model for bambara groundnut to predict growth, development and yield under drought, heat and cold stress and different daylengths. The present model (BAMGRO) is an adaptation of the established CROPGRO and previous bambara groundnut models; BAMnut and BAMFOOD project model. It uses climate data, landrace specific parameters and soil characteristics and runs on a daily time-step to determine the canopy development, biomass production and yield of a landrace in a specific environment. The parameters of the model have been determined with glasshouses data (TCRU, University of Nottingham) and published information. BAMGRO is capable of describing differences between landraces, and the influence of drought, temperature and photoperiod using a simplified approach.